Estimation of Directional Wave Spectrum Using Measurement Array Pressure Data on Bottom-Mounted Offshore Structure in Incident and Diffracted Wave Field - Xiaodong Song; Zilong Ti; Yuanzhou Zhou (Shock and Vibration)
Determination of the directional wave spectrum which offshore structures actually encounter is essential for multiple applications including wave-induced load and vibration evaluation, and hence becomes a fundamental task in ocean engineering. Due to the wave diffraction effect, wave field around an offshore structure is the mixture of incident wave components and diffracted wave components. Estimating directional wave spectrum in diffracted wave field significantly differs from the occasion in undisturbed waves since the amplitude and phase relationship between the incident and diffracted waves are coupled, and therefore making the conventional approach not applicable. In this study, the diffraction wave theory is introduced into the estimation of directional wave spectrum to consider the effect of diffracted waves using array pressure data from existing pressure gauges on structures. Considering the performance of the presented approach under scenarios with various gauge arrays, different directions, and spreading coefficients, multiple levels of background noise are evaluated and discussed, respectively. The presented approach is also deployed into an in-situ measurement application on a marine structure and compared with wave observation data to test its feasibility in engineering practice. In general, the presented approach can reasonably estimate the directional wave spectrum and show advantages over the conventional approach in which the diffraction effect is excluded.